Evaluating the level of organizational commitment and its relationship to discipline doctors: an analytical study of the opinions of a sample of doctors in Teaching Remade Hospital - النعيمي شهاب الدين حمد; الهيتي محمود اسماعيل (Journal of Economics and Administrative Sciences, 2016)
The aims of this reserch is identify evaluate the organizational commitment level of (emotional, standard, continuous) and the level of discipline dimensions (functional duties, professional responsibility and ethics) for medical doctors in Ramadi Teaching Hospital due to their relationship with the organization effectiveness the level of completion work and the importance of the expected results in the field respondent sample of (50) doctors has from all branches and specialties, including specialist doctors consultants and practitioners as well as branches of residence and senior the most prominent results reached are the emotional and the standard commitments are above average level continuous commitment appeared to be weak because of the gravity of the security situation and there is a strong influence of organizational commitment in the discipline of doctors